2018
DOI: 10.3390/ijms19041129
|View full text |Cite
|
Sign up to set email alerts
|

An Organic Solvent-Tolerant Lipase with Both Hydrolytic and Synthetic Activities from the Oleaginous Fungus Mortierella echinosphaera

Abstract: Lipase enzymes of the oleaginous fungal group Mortierella are rarely studied. However, considering that most commercial lipases are derived from filamentous fungal sources, their investigation can contribute to the cost-effective development of new biotechnological processes. Here, an extracellular lipase with a molecular mass of 30 kDa was isolated from Mortierella echinosphaera CBS 575.75 and characterized. The purified lipase exhibited an optimal p-nitrophenyl palmitate (pNPP)-hydrolyzing activity at 25 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…There were five R. microsporus strains with notable activity in the Rhizopus group, and one isolate of M. echinosphaera and M. globulifera with promising β-galactosidase production were identified among Mortierella . It is worth mentioning that the same M. echinosphaera was found to be an excellent producer of a lipase with transesterification activity in our previous research [ 25 ]. The combined application of β-galactosidases and lipases can result in sugar–lactate copolymer biomaterials under appropriate conditions [ 26 ] and the possibility to utilize the two biocatalysts from a same organism is a particularly ecofriendly way.…”
Section: Discussionmentioning
confidence: 99%
“…There were five R. microsporus strains with notable activity in the Rhizopus group, and one isolate of M. echinosphaera and M. globulifera with promising β-galactosidase production were identified among Mortierella . It is worth mentioning that the same M. echinosphaera was found to be an excellent producer of a lipase with transesterification activity in our previous research [ 25 ]. The combined application of β-galactosidases and lipases can result in sugar–lactate copolymer biomaterials under appropriate conditions [ 26 ] and the possibility to utilize the two biocatalysts from a same organism is a particularly ecofriendly way.…”
Section: Discussionmentioning
confidence: 99%
“…Geotrichum (OtuF0003) has been reported to be cultivated on hydrophobic substrates being capable of secreting extracellular lipases (Hlavsová et al, 2009) and assimilating carbon sources such as fats and oils to use them for growth and storage (Papanikolaou et al, 2017;. The same occurs with Mortierella (OtuF0004), also reported being able to secrete lipases (Jermsuntiea et al, 2011;Kotogán et al, 2018) and produce lipids from hydrophobic substrates such as triolein or sesame oil (Papanikolaou and Aggelis, 2019). However, Apiotrichum (OtuF001) has been only identified as capable of growing and storing lipids on hydrophilic substrates (Papanikolaou and Aggelis, 2011a;Park et al, 1990;Qian et al, 2021;Ykema et al, 1989) and it has not been reported as a lipase producer.…”
Section: Selection Of Storing Compounds and Microbial Populations Cor...mentioning
confidence: 97%
“…BatA required buffer systems with alkaline pH values (pH 8.0), which is a typicial feature for enzymes of the mitochondrial matrix [32] (Figure S4). Its temperature optimum of 25 • C is characteristic for enzymes from cryophilic fungi such as Mortierellaceae [33]. The enzyme converted all BCAAs (L-Ile, L-Leu, L-Val) and their respective α-keto acids in a PLP-dependent manner (Figure 5A-G and Figure S5).…”
Section: Biochemical Characterization Of Batamentioning
confidence: 99%